2014
DOI: 10.1007/s00432-014-1871-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically silenced long noncoding-SRHC promotes proliferation of hepatocellular carcinoma

Abstract: Here, we identified a new long noncoding RNA designated as SRHC that is capable of inhibiting cancer proliferation and is down-regulated in tumors at least partly by DNA methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Aberrant hypermethylation of specific CpG islands can lead to the silencing of tumor suppressor genes involved in key cellular pathways [17]. Promoter hypermethylation may be partly responsible for the downregulation of some lncRNAs including MEG3, H19, SRHC and CAHM in carcinoma [18][19][20][21]. To gain insight into the expression profile of lncRNA in GCA, we investigated the microarray expression profile of lncRNA transcriptome in 5 GCA tissues and 5 paired corresponding normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant hypermethylation of specific CpG islands can lead to the silencing of tumor suppressor genes involved in key cellular pathways [17]. Promoter hypermethylation may be partly responsible for the downregulation of some lncRNAs including MEG3, H19, SRHC and CAHM in carcinoma [18][19][20][21]. To gain insight into the expression profile of lncRNA in GCA, we investigated the microarray expression profile of lncRNA transcriptome in 5 GCA tissues and 5 paired corresponding normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al found that inhibition of lncRNA SRHC could promote the proliferation of HCC cells and was significantly correlated with a high serum a-fetoprotein level and a low degree of differentiated tumors. Mechanistic analysis of the SRHC downregulation indicated that the promoter region of SRHC contains a CpG-rich island and SRHC is down-regulated in tumors by DNA methylation, suggesting lncRNA might be crucial in methylation-modified phenotype of HCC [63]. LncRNA-MEG3 (maternally expressed gene 3) was down-regulated in HCC and acted as a tumor suppressor for both anchorage-dependent and -independent cell growth.…”
Section: Long Noncoding Rna and Dna Methylationmentioning
confidence: 99%
“…It is known that lncRNAs can promote or suppress cell death pathways through diverse molecular mechanisms including epigenetically silencing (Zheng et al, 2014), acting as sponge or precurors for miRNAs , activating or inhibiting signal molecules and interacting with protiens or nucleic acids in various cell types. For example, recently one lncRNA named PANDAR (promoter of CDKN1A antisence DNA damage-activated RNA) is reported to interacts with the transcription factor NF-YA to limit the expression of pro-apoptotic genes in lung cancer cell lines.…”
Section: Lncrnas and Cell Deathmentioning
confidence: 99%